Dual-function ZIF-8 membrane supported on alumina hollow fiber membrane for copper(II) removal - Dayang Norafizan, Awang Chee; Farhana, Aziz; Ahmad Fauzi, Ismail; Mohamed Afizal, Mohamed Amin; Mohd. Sohaimi, Abdullah (Elsevier Ltd., 2021)
The as-spun alumina hollow fiber membrane was used as membrane support for the development of ZIF-8 membrane. The ZIF-8 layers were successfully grown on the support by using the in-situ solvothermal method and layer-by-layer method. The morphology and physicochemical properties of the membranes were characterized using the field emission scanning electron microscope (FESEM), X-ray diffraction spectrophotometer (XRD), Fourier-Transform Infrared Spectrophotometer (FTIR). The adsorption study revealed that the removal of copper(II) ion was pH-dependent. The adsorption capacity for copper(II) adsorption is 76.5 mg/g. The adsorption mechanism of copper(II) onto the ZIF-8 membrane was best fitted to the Freundlich isotherm and pseudo-second-order model. The filtration study showed that the membranes could remove up to 90% of copper(II) ions from the aqueous solution.